The Influence of Motivation, Training, and Work Environment on Employee Job Satisfaction at PT. PLN Nusa Daya Balikpapan - Wardani, Chandra Aditya; Ariani, Misna; Arrywibowo SU, Imam (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2025)
The purpose of this study is to determine the effect of motivation, training and work environment on job satisfaction of employees of PT PLN Nusa Daya Balikpapan. The type of research used is quantitative research. The sampling technique in this research uses purposive sampling with a population of 62 employees, then the sample taken in this research is employees of PT PLN Nusa Daya Balikpapan totaling 46 employees at MCU ON SITE Balikpapan Head Office which will be used as the research sample size. Data collection method is done by distributing questionnaires. This research uses multiple linear regression with the help of SmartPLS in processing data. The result of this study shows that motivation variable has partial effect on job satisfaction of PT PLN Nusa Daya Balikpapan employees, training variable has partial effect on job satisfaction of PT PLN Nusa Daya Balikpapan employees, and work environment variable has partial effect on job satisfaction of PT PLN Nusa Daya Balikpapan employees. Keywords: Motivation; Training, Work Environment; Job Satisfaction